2017
DOI: 10.5812/archcid.57290
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mutations in Topoisomerase Genes and the Plasmid-Mediated Quinolone Resistance (PMQR) Determinants on the Resistance to Fluoroquinolones in Klebsiella pneumoniae

Abstract: Background: Klebsiella pneumoniae causes a variety of infections including community acquired pneumonia and nosocomial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
4
0
1
Order By: Relevance
“…Additionally, the aac(6ʹ)-Ib-cr gene was observed more frequently than qnr genes among Enterobacteriaceae clinical isolates in different previous studies. 2,26,35,36 This comes to support our result.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, the aac(6ʹ)-Ib-cr gene was observed more frequently than qnr genes among Enterobacteriaceae clinical isolates in different previous studies. 2,26,35,36 This comes to support our result.…”
Section: Discussionsupporting
confidence: 88%
“…Similar high-prevalence rate for mutations in gyrA has been reported by Alisha et al from Iran and Muthu et al from India. 18,19 Although the gyrA and parC are most commonly reported, mutation-resistant genes in the QRDR regions, in the current study, gyrB and parE genes were also frequently encountered.…”
Section: Discussionmentioning
confidence: 52%
“…Akya et al reported that K. pneumoniae strains carrying qnrB have MICs from 32 to 128 μg/ml for Ciprofloxacin (except one strain which has an MIC between 4 and 16 μg/ml). Those authors also noticed the strains that carried qnrB and qnrS together had even higher MICs (≥256 μg/ml) for ciprofloxacin [ 24 ]. Our findings for qnrB differed from those of the study by Akya et al However, it was clear that strains carrying qnrA has a higher MIC [24].…”
Section: Discussionmentioning
confidence: 99%